KEHIDUPAN SOSIAL EKONOMI PENGRAJIN MUDA TENUN SIAK DI KECAMATAN SIAK - Ari Kurnia; Syafrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in the village of Kampung Rempak Siak, Siak District, Siak Regency. The purpose of this study was to find out the social life of young Siak weaving craftsmen and to find out the economic life of young Siak weaving craftsmen. The research subjects involved in this study were 4 craftsmen and 1 key informant, namely the owner of a weaving business in the village of Kampung Rempak Siak, Siak District, Siak Regency. This research use desciptive qualitative approach. The methods used are observation, documentation and in-depth interviews using three elements, namely data reduction, presentation and conclusion. From the results of the research conducted, it shows that: 1) The social life of young weaving craftsmen when viewed from the factors behind becoming craftsmen is due to economic factors and also because the work is relaxed and there is no pressure. Where in everyday life communication and relations between workers and workers with owners are very good. Where workers respect each other and also have good ethics and help each other if a colleague needs help, however, under no matter how good the conditions, conflict will still occur, whether it's a scramble in making woven motifs or other things. The working time is determined by the worker so that each worker determines the working time in a different day. Likewise for vacation time every month the owner gives 4 times off, each worker may take all of it or not. 2) The economic life of young weaving craftsmen when viewed from their monthly income is around Rp. 500,000 – Rp. 3,000,000, the amount of this income depends on the amount of woven cloth produced. With the income earned by workers being able to meet their daily needs, this is helped because the owner provides housing and other facilities. For long-time workers, they are able to set aside their income to save. Keywords: Weaving Craftsmen, Social Life and Economic Life